SOCIO-CULTURAL ENVIRONMENT AT THE UNIVERSITY - Svetlana A. Ostrikova; Tatiana V. Nikulina (Высшее образование в России)
This paper addresses the system approach to the formation of the social and cultural environment at Belgorod State National Research University (NRU «BelSU »). The authors consider the basic components of the model of the identity of university graduating student, the main directions and forms of educational activity and extra curricular activities. Special attention is paid to the important aspects of health oriented educational system.